Comparative Effectiveness and Safety of Direct Oral Anticoagulants Versus Warfarin for Stroke Prevention and Major Bleeding in Atrial Fibrillation: A Systematic Review and Network Meta-Analysis - Mian Zahid Jan Kakakhel (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Atrial fibrillation (AF) is one of the most common arrhythmias, affecting over 52 million people worldwide. Direct-acting oral anticoagulants (DOACs) are proposed as add-on therapy to prevent ischemic stroke in AF. Purpose: To assess the safety of various DOAC regimens compared with warfarin in AF patients. Methods: A literature search across four databases (inception–January 2025) identified randomized trials comparing DOACs and warfarin. Outcomes included stroke, intracranial haemorrhage (ICH), all-cause mortality, major bleeding, and non-ICH mortality. Risk ratios (RR) with 95% credible intervals (CrI) were estimated. Surface under the cumulative ranking curve (SUCRA) indicated lowest event risk. Analyses used the Bugsnet package in R with a common-effects model and deviance information criterion. Results: Eighteen studies with 89,985 patients and nine treatment arms were analyzed. Rivaroxaban 15 mg once daily (OD) showed the lowest stroke risk (RR 0.45; 95% CrI 0.20–0.92; SUCRA 83.15%), followed by dabigatran 150 mg twice daily (BD) (RR 0.68; 95% CrI 0.55–0.84) and apixaban 5 mg BD (RR 0.74; 95% CrI 0.62–0.89). Major bleeding risk was lowest but not significant with apixaban 2.5 mg (SUCRA 86.68%); significant reduction occurred with apixaban 5 mg BD versus warfarin (RR 0.70; 95% CrI 0.62–0.91). Rivaroxaban 15/20 mg OD carried the highest major-bleeding risk, exceeding that of dabigatran 110 mg BD and apixaban 5 mg BD. For ICH, dabigatran 110 mg BD had the lowest risk (SUCRA 92.81%), significantly lower than apixaban 5 mg BD, rivaroxaban 15/20 mg OD, and warfarin. Mortality unrelated to ICH was lowest with endoxaban 60 mg OD, followed by dabigatran 150 mg BD and apixaban 5 mg BD; all DOACs outperformed warfarin. All-cause mortality was least with endoxaban 60 mg OD, then apixaban 5 mg BD and dabigatran 150 mg BD. Conclusion: Apixaban 5 mg provides the best overall safety, combining low major-bleeding risk with favorable stroke and mortality outcomes. Rivaroxaban 15 mg offers the greatest stroke protection. Overall, all DOACs were safer and at least as effective as warfarin.